Meningkatkan Hasil Belajar Senam Lantai Roll Depan Melalui Metode Pembelajaran Koperatif Tipe Jigsaw Kelas VIII-A SMP Negeri 3 Gorontalo - Alamri, Moh Padel; Bantahali, Rahmad; Dama, Adriyanto; Rusman, Kasmir; Hidayat, Joni Taufik; Ikhsan, Haerul; Ilham, Al (Universitas Negeri Gorontalo, 2025)
His study aims to improve the results of floor gymnastics learning for front rolls through the cooperative learning method of the jigsaw type for eighth-grade students in class VIII-A at SMP Negeri 3 Gorontalo. The method used in this research is Classroom Action Research (CAR). The research design involves a procedural framework in a classroom action research conducted in stages. The data analysis results show that in cycle I, the average student achievement score is 66.94, categorized as good. After implementing corrective actions in cycle II, there was a significant improvement with an average score reaching 80.56, categorized as very good or optimal. These findings indicate that using the jigsaw type of cooperative learning method in teaching has an impact on improving the learning outcomes of floor gymnastics for front rolls.